PENGEMBANGAN MODUL PEMBELAJARAN SISTEM REPRODUKSI BERBASIS PROBLEM SOLVING UNTUK SISWA SMA N 1 UMBUNASI KELAS XI-IPA - Giawa, Ismael Putra (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
The unavailability of learning modules that can stimulate student learning motivation is a serious obstacle in the learning process because it greatly influences student motivation and learning outcomes. This study aims to develop a problem solving-based reproductive system learning module. This type of research is research and development (Research and Development) using the 4D development method. This research was tested on 20 students of class XI-IPA at SMA Negeri 1 Umbunasi. In order to standardize the product, there are three test stages, namely validity test, practicality test and effectiveness test. The instrument used is a research questionnaire using a Likert scale and evaluation test questions to determine student learning outcomes. The results of the study show that the problem solving based learning module is very valid with a percentage of 94.1% and is feasible to use. The average value of practicality by teachers is 3.7% and students are 3.8% in the very practical category. The results of student motivation were at 95.5% with an average cognitive score of 88.7 compared to before using the problem solving-based learning module with an average score of 58.8 in the sufficient category. The suggestions put forward by the researcher are 1) Through this learning module students can utilize good learning resource materials in order to increase their knowledge and their learning outcomes continue to increase. 2) Biology subject teachers should be able to use this problem solving-based learning module in the learning process because it can increase student motivation and learning outcomes. 3) For future researchers, this problem solving-based learning module can be used as a reference in relevant research.